Asthma control in severe asthmatics under treatment with omalizumab: A cross-sectional observational study in Italy. (April 2015) - Novelli, Federica; Latorre, Manuela; Vergura, Letizia; Caiaffa, Maria Filomena; Camiciottoli, Gianna; Guarnieri, Gabriella; Matucci, Andrea; Macchia, Luigi; Vianello, Andrea; Vultaggio, Alessandra; Celi, Alessandro; Cazzola, Mario; et al.
Abstract: Few data are available on the proportion of asthmatics achieving a good asthma control (according GINA guidelines) and on the level of airway inflammation during omalizumab treatment. The aim of this cross-sectional national observational study was to assess the level of control (according to GINA guidelines) achieved in a group of asthmatics on omalizumab treatment, and to characterize the factors that influence the lack of control. We studied 306 asthmatics under omalizumab treatment for a median of 32 months (range 4–120). The level of control according to GINA was good in 25.2%, partial in 47.1% and poor in 24.5% of patients (data were missing for the remaining 3.2%). Comparison between poorly controlled and partially or well controlled asthmatics showed a statistically significant higher prevalence of some comorbidities in the first group, namely obesity, gastro-oesophageal reflux disease (GORD), aspirin intolerance and mental disorders (all p  < 0.001). Similarly, asthmatics with at least one exacerbation in the last year showed a significantly higher prevalence of obesity, chronic rhinosinusitis, nasal polyps, GORD, and aspirin intolerance (all p  < 0.05) than patients without exacerbations. When we selected patients without relevant comorbidities (upper airways disease, GORD, obesity, aspirin intolerance) and not currently smoking ( N  = 73), the percentage of well or partially controlled asthmatics was significantly higher than in patients with comorbidities (84.9% vs 71.1%, p  = 0.02); the rate of asthmatics without exacerbations in the last year was also higher (73.6% vs 51.1%, p  = 0.001). During omalizumab treatment, a high percentage of asthmatics obtain a good or partial control of asthma. Comorbidities are associated with the lack of asthma control and persistence of exacerbations.